Public health implications of the re-emergence of ‘Chandrabora’ or ‘Ulobora’ (Russell’s viper) envenoming in Bangladesh (Bangladesh Journal of Medicine, 2024)
Abstract not availableBangladesh J Medicine 2024; 35: 129-132